(3JfRjg GdCfHjGAs - (3GdTQja GdeQJVis; (3CHh GdbGSe Ydj Hf GdMSjf Hf ehSi GdTQja GdeQJVj, GdTQja GdeQJVj,J (B436 (3g` s
(3ChdgG (B:s
(3jMOK GdESfGO Yf CejQ GdeDefjf Ydi Hf CHj WGdH Ydjg GdSdGe bGd(B: (3bGd QShd Gddg Udi Gddg Ydjg hBdg(B: (((3eG Ndb Gddg JYGdi CaVd ef CeJi, hdG CcQe Ydjg efi s
(3BNQgG (B:s
(3Je GdcJGH hGdMeO ddg hMOg, hUdhGJg Ydi SjOfG eMeO hBdg GdWjHjf GdWGgQjf, hGdMeO ddg s
(3aj fgGjI GdeNWhW COYjI hCPcGQs
(3HebOGQ (B10 (3hQbGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B81s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds